Report on the western section of the proposed Pacific and Hudson Bay Railway Company [electronic resource] - Kyle, G. A. (George Allan), 1837-1924.; Harris, E. C.; Cartwright, C. E. (Conway Edward), 1864-1938. ([Vancouver? : s.n.], 1912)
Tables. Electronic reproduction. Mode of access: Internet. 44